PEMBANGUNAN JURASSIC PARK DI PULAU KOMODO BERDASARKAN WORLD HERITAGE CONVENTION 1972 - Irfanto Norchamahdi; Amalia Zuhra (Reformasi Hukum Trisakti, 2023)
In 2020 a Geopark will be built that carries the Jurassic Park concept which has caused a lot of polemic in the community, whether the development is said to violate the provisions of the World Heritage Convention. This requires the government to make efforts to preserve the Komodo dragon as an endangered species. The problem is whether the construction of the Komodo Island Jurassic Park violates the provisions of the 1972 World Heritage Convention and what efforts need to be made to protect and preserve Komodo dragons? The article is normative research methods were carried out. Data processing is done qualitatively and conclusions is done using deductive methods. The results of the research and discussion are that the development of the Komodo National Park is an integrated and well-planned planned infrastructure regeneration which includes the design of areas, routes, supply of clean water, waste management, cleaning, and rejuvenation of human settlements. Jurassic Park Komodo National Park will not have a negative impact but a positive impact because the goal is to protect the diversity of the earth through conservation. 5 of 1990 concerning the Conservation of Living Natural Resources and their Ecosystems.